2003
DOI: 10.1590/s0102-311x2003000500022
|View full text |Cite
|
Sign up to set email alerts
|

Relacionamento violento na adolescência e risco de DST/AIDS

Abstract: To verify whether affective relationships involving violence are associated with increased risk of sexually transmitted diseases (STDs), including AIDS, we conducted a survey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 6 publications
1
14
0
14
Order By: Relevance
“…In a study on sexual coercion, risk factors are lower educational level of the mother and of adolescent boys and girls, but especially of adolescent girls (Moraes et al, 2006); unemployment (Taquette et al, 2003) Low educational achievement of women/ girls (ENDESA, 2013) Harmful substance use (Vagi et al, 2013;Lundgren and Amin, 2015;Nowotny & Graves, 2013;Johnson, 2000) Young women who drink heavily, whether infrequently or frequently, have greater odds of experiencing sexual only or sexual and physical IPV compared to abstainers (Waller et al, 2012) Adolescent girls who experience IPV also exhibit other health risk behaviors. According to a representative epidemiologic study (lifetime prevalence of dating violence among U.S. adolescents, controlling for the effects of potentially confounding demographics and risk behaviors): physical and sexual dating violence against adolescent girls is associated with increased risk of substance use, unhealthy weight control behaviors, sexual risk behaviors, pregnancy, and suicidality Drug and alcohol use (Taquette et al, 2003) Substance abuse (men who suffered from alcohol abuse reported more IPV perpetration and victimization in comparison to those who did not consume alcohol; women who suffered from alcohol abuse reported suffering and perpetrating more physical and psychological violence than those who did not) (ENDESA, 2013) Family-related factors: Family conflict, poor parent-child relationships, witnessing violence (Vagi et al, 2013); Witnessing or being a victim of violence (Lundgren and Amin, 2015) Childhood exposure to violence is a consistent predictor of involvement in relationships with IPV for both males and females (referring to dating violence among adolescents and college students in the US) (Gover, Kaukinen & Fox, 2008) Associated factors, both for experiencing and using adolescent IPV included previous experiences of child maltreatment, domestic violence in the family (Barter et al, 2009) Adolescents exposed to marital violence during childhood were more likely to justify the use of violence in dating relationships (Lichter & McCloskey, 2004).…”
Section: Research Monitoring and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on sexual coercion, risk factors are lower educational level of the mother and of adolescent boys and girls, but especially of adolescent girls (Moraes et al, 2006); unemployment (Taquette et al, 2003) Low educational achievement of women/ girls (ENDESA, 2013) Harmful substance use (Vagi et al, 2013;Lundgren and Amin, 2015;Nowotny & Graves, 2013;Johnson, 2000) Young women who drink heavily, whether infrequently or frequently, have greater odds of experiencing sexual only or sexual and physical IPV compared to abstainers (Waller et al, 2012) Adolescent girls who experience IPV also exhibit other health risk behaviors. According to a representative epidemiologic study (lifetime prevalence of dating violence among U.S. adolescents, controlling for the effects of potentially confounding demographics and risk behaviors): physical and sexual dating violence against adolescent girls is associated with increased risk of substance use, unhealthy weight control behaviors, sexual risk behaviors, pregnancy, and suicidality Drug and alcohol use (Taquette et al, 2003) Substance abuse (men who suffered from alcohol abuse reported more IPV perpetration and victimization in comparison to those who did not consume alcohol; women who suffered from alcohol abuse reported suffering and perpetrating more physical and psychological violence than those who did not) (ENDESA, 2013) Family-related factors: Family conflict, poor parent-child relationships, witnessing violence (Vagi et al, 2013); Witnessing or being a victim of violence (Lundgren and Amin, 2015) Childhood exposure to violence is a consistent predictor of involvement in relationships with IPV for both males and females (referring to dating violence among adolescents and college students in the US) (Gover, Kaukinen & Fox, 2008) Associated factors, both for experiencing and using adolescent IPV included previous experiences of child maltreatment, domestic violence in the family (Barter et al, 2009) Adolescents exposed to marital violence during childhood were more likely to justify the use of violence in dating relationships (Lichter & McCloskey, 2004).…”
Section: Research Monitoring and Evaluationmentioning
confidence: 99%
“…According to a representative epidemiologic study (lifetime prevalence of dating violence among U.S. adolescents, controlling for the effects of potentially confounding demographics and risk behaviors): physical and sexual dating violence against adolescent girls is associated with increased risk of substance use, unhealthy weight control behaviors, sexual risk behaviors, pregnancy, and suicidality Drug and alcohol use (Taquette et al, 2003) Substance abuse (men who suffered from alcohol abuse reported more IPV perpetration and victimization in comparison to those who did not consume alcohol; women who suffered from alcohol abuse reported suffering and perpetrating more physical and psychological violence than those who did not) (ENDESA, 2013) Family-related factors: Family conflict, poor parent-child relationships, witnessing violence (Vagi et al, 2013); Witnessing or being a victim of violence (Lundgren and Amin, 2015) Childhood exposure to violence is a consistent predictor of involvement in relationships with IPV for both males and females (referring to dating violence among adolescents and college students in the US) (Gover, Kaukinen & Fox, 2008) Associated factors, both for experiencing and using adolescent IPV included previous experiences of child maltreatment, domestic violence in the family (Barter et al, 2009) Adolescents exposed to marital violence during childhood were more likely to justify the use of violence in dating relationships (Lichter & McCloskey, 2004). However it is also noteworthy that, traditional attitudes about male-female relationships and justifying relationship violence were associated with higher levels of adolescent IPV perpetration regardless of marital violence exposure.…”
Section: Research Monitoring and Evaluationmentioning
confidence: 99%
“…A common thread among these is that different types of aggression are frequently deemed acceptable or, at least, quite natural, among adolescents. This has further promoted violence in intimate relations as a means of resolving conflict, particularly under conditions of jealousy [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Muitos estudos sobre HIV, ao abordar a população adolescente, exploram questões importantes, como a prevenção do contágio do vírus [3][4][5] ou os fatores de risco ou de proteção para o contágio do HIV 6,7 . Entretanto, poucas são as pesquisas que enfocam os adolescentes contaminados, em especial os seus aspectos psicológicos [8][9][10] .…”
Section: Introductionunclassified